The creation of God - Pinxten, Rik.; ebrary, Inc. (Bruxelles ; New York : P.I.E. Peter Lang, 2010)
"This book develops a scientific approach to the phenomenon of religion. It is the conviction of the author that such an approach can only be comparative in nature, in order to overcome centuries of religiously-biased views on religion."--Publisher.
Religion : a first approach -- Old and new models -- Science and religion : where do I stand? -- Religion, identity and learning processes -- General concepts and terms -- Cosmology and religion -- Religious action -- Different 1. Birth and baptism. A view of an anthropologist and atheist -- Religious language -- Complex religious phenomena -- Religious ways of learning -- Different 2. Genesis in the Bible. The creation of heaven and the earth -- Religious artifacts -- Politics, ethics and fundamentalism -- Atheistic religiosity?.
"First edition, fully updated here, appeared as Goddelijke Fantasie, Antwerp, Belgium with Houtekiet Publ. in 2000."--T.p. verso.
Includes bibliographical references.
Electronic reproduction.
Keywords: Religion; Electronic books